3-total edge product cordial labeling of some new classes of graphs. Issue 3 (3rd April 2018) - Yan, Li; Li, Yingfang; Zhang, Xiujun; Saqlain, Madiha; Zafar, Sohail; Farahani, Mohammad R.
Abstract: In this paper we study 3-total edge product cordial (3-TEPC) labeling of some new classes of graphs. We study ladder graph, wheel graph, m isomorphic copies of n –cycle graph and dutch windmill graph in the context of 3-TEPC labeling. We also studied 3-TEPC labeling of some particular examples of graph operations like corona graphs and subdivision graphs.